2017
DOI: 10.1016/j.ajpath.2017.04.007
|View full text |Cite
|
Sign up to set email alerts
|

Macrophages Regulate Unilateral Ureteral Obstruction-Induced Renal Lymphangiogenesis through C-C Motif Chemokine Receptor 2–Dependent Phosphatidylinositol 3-Kinase-AKT–Mechanistic Target of Rapamycin Signaling and Hypoxia-Inducible Factor-1α/Vascular Endothelial Growth Factor-C Expression

Abstract: Lymphangiogenesis occurs during renal fibrosis in patients with chronic kidney diseases and vascular endothelial growth factor (VEGF)-C is required for the formation of lymphatic vessels; however, the underlying mechanisms remain unclear. We demonstrate that macrophages can regulate unilateral ureteral obstruction (UUO)-induced renal lymphangiogenesis by expressing high levels of VEGF-C by C-C motif chemokine receptor 2 (CCR2)-mediated signaling. Mice deficient in Ccr2 manifested repressed lymphangiogenesis al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 39 publications
1
27
1
Order By: Relevance
“…Our results seem inconsistent with gene expression in patients. This demonstrates the complexity of a whole tumor, the role of the tumor microenvironment, blood, lymphatic and immune systems and of phenomena such as hypoxia, which are not totally understood yet [59][60][61] . The effect of tumor microenvironment has previously been demonstrated in the lab.…”
Section: Discussionmentioning
confidence: 96%
“…Our results seem inconsistent with gene expression in patients. This demonstrates the complexity of a whole tumor, the role of the tumor microenvironment, blood, lymphatic and immune systems and of phenomena such as hypoxia, which are not totally understood yet [59][60][61] . The effect of tumor microenvironment has previously been demonstrated in the lab.…”
Section: Discussionmentioning
confidence: 96%
“…The two molecules have also been significantly associated with HIF-1α expression in various cancers through immunohistochemical techniques [106,107]. Molecular analysis showed that hypoxic conditions determines the transcription at mRNA level of VEGF-C and VEGF-D in lymphatic endothelial cells [108], where in macrophages, HIF-1α can manage the expression of VEGF-C via a hypoxia response element (HRE) sequence located within the promoter of the VEGF-C gene [109]. The expression of the same gene in hypoxia can be induced also independently of HIF-1α regulation through a mechanisms dependent of an internal ribosome entry site [110].…”
Section: Hypoxia and The Genesis Of New Blood Vessels: The Modulationmentioning
confidence: 99%
“…There is a decrease in renal blood flow and glomerular filtration rate (GFR) during the first 3 h after UUO, followed by a progressive increase in interstitial inflammatory cell inflltration occurring 12 h to 14 days after the obstruction and by day 3, inflammation, microvascular damage and increased numbers of fibroblasts are apparent ( 12 ). Interstitial fibrosis occurs between days 5 and 12 and reaches its peak on day 19 ( 13 ).…”
Section: Introductionmentioning
confidence: 99%